One-step and real-time detection of Hg2+ in brown rice flour using a biosensor integrated with AC electrothermal enrichment. (1st August 2023) - Qi, Haochen; Xiao, Lei; Wu, Jayne; Lv, Li; Hu, Xinyu; Zhuang, Youyi; Liu, Xiaoru; Zhao, Wenci; You, Fangshuo; Zhang, Jian; Zheng, Lei
Highlights: A biosensor for one-step detection of Hg 2+ in food with a response time of 30 s. A detection limit of 1.114 fM, a linear range up to 0.1 nM and good selectivity. Successful detection of Hg 2+ in quality control brown rice flours. Easy to operate, without label, signal amplification and extra enrichment steps. Abstract: Mercury (Hg 2+ ) is one of the most toxic heavy metals in farm products, so rapid detection of trace Hg 2+ has always been sought after with high interest. Herein, we report a biosensor to specifically recognize Hg 2+ in leaching solutions of brown rice flour. This sensor is simple and of low cost, with a very short assay time of 30 s. Another merit is the ultra-low limit of detection (LOD) at fM level. In addition, the specific aptamer probe realizes a good selectivity above 10 5 : 1 against the interferences. This sensor is developed based on an aptamer-modified gold electrode array (GEA) for capacitive sensing. Alternating current electrothermal (ACET) enrichment is induced during the AC capacitance acquirement. Thus, the enrichment and detection are coupled as a single step, and pre-concentration is needless. Owing to the sensing mechanism of solid–liquid interfacial capacitance and ACET enrichment, Hg 2+ level can be sensitively and rapidly reflected. Also, the sensor has a wide linear range from 1 fM to 0.1 nM and a shelf life of 15 days. This biosensor shows advantages on overall performance, enabling easy-to-operate, real-time, and large-scale Hg 2+ detection in farm products.